2008
DOI: 10.1136/vr.163.5.139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory investigations of the outbreaks of foot‐and‐mouth disease in southern England in 2007

Abstract: A case of foot-and-mouth disease (fmd) on a cattle farm in Normandy, Surrey, was confirmed on Friday August 3, 2007, the first case in the uk since 2001. The infection was detected nearby on a second farm on August 6. On September 12, fmd was confirmed on a farm approximately 20 km from Normandy in Egham, and this was followed by cases on five more farms in that area in the next three weeks. The majority of the infected farms consisted of multiple beef cattle holdings in semi-urban areas. In total, 1578 animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…Clinical signs (acute fever, anorexia, vesicular lesions in the mouth and feet of infected animals with consequent excessive salivation, lameness and reduced productivity) determined in this study were in agreement with those reported for FMD [6,[11][12][13] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Clinical signs (acute fever, anorexia, vesicular lesions in the mouth and feet of infected animals with consequent excessive salivation, lameness and reduced productivity) determined in this study were in agreement with those reported for FMD [6,[11][12][13] .…”
Section: Discussionsupporting
confidence: 81%
“…However, even in some breeds of cattle, FMD can also be clinically difficult to recognize because of the mild appearance of the disease [10] . The disease is typically characterized by acute fever and the development of vesicular lesions in the mouth and feet of infected cloven-hoofed animals (principally cattle, pigs, sheep and goats) with consequent excessive salivation, anorexia, lameness, mortality of young animals and reduced productivity [10][11][12][13] . Foot-and-mouth disease usually has a high morbidity and low mortality, with mortality occurring mostly in young animals [6] .…”
Section: Introductionmentioning
confidence: 99%
“…This plasmid contained the target sequences of both the one step real-time RT-PCR assay used in this study [15] as well as the region amplified by the RT-LAMP assay [24]. The resultant viral RNA was resuspended in DEPC treated water and quantified at A 260 using a NanoDrop ND-1000 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…The RT-PCR assay used was a one-step assay that amplifies a 107 nucleotide fragment within the highly conserved 3D region of the FMDV genome, as previously described [15]. All samples assayed using this method were tested in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation